Desenvolvimento de métodos de pré-concentração para a determinação de elementos traço e especiação de cromo e arsênio em amostras agrícolas - Sá, Ívero Pita de (Universidade Federal de São Carlos, 2021)
Agricultural sustainable production is indispensable to meet the growing demand for food and nutritional control. The risk assessment associated with contamination by toxic elements in agricultural and aquaculture matrices are essential. In this context, the present thesis evaluated new methodologies for pre-concentration and chemical speciation methods using different determination techniques, such as microwave-induced plasma optical emission spectrometry (MIP OES), liquid chromatography associated with inductively coupled plasma mass spectrometry (LC-ICP-MS), flame atomic absorption spectrometry (FAAS) and spectrophotometry (UV-VIS) for analysis of fish and organic fertilizer samples. Solid-phase extraction (SPE) for As, Cd, Cr, Cu, Hg, Pb and Zn determination in meat and fish, and co-precipitation for As and Cd determination in fish were the pre-concentration procedures used to increase the sensitivity of the MIP OES. Experimental planning was applied to optimize the methods, being the trueness evaluated with analysis of certified reference materials (CRMs) and comparison with another instrumental technique, ICP-MS. The values found agreed with reference values, demonstrating the feasibility of the methods. The chemical speciation of As and Cr in fish was performed by LC-ICP-MS, and the extraction of the species was defined using experimental designs. The trueness of the procedures was verified by the analysis of four CRMs and with addition and recovery experiment. Finally, a method for speciation of Cr(VI) in organic fertilizer was developed. The method proved to be adequate for determination by FAAS and UV-VIS. It provided limits of detection of 1.4 and 1.8 mg/kg, respectively, lower than 2.0 mg/kg, the maximum value allowed by the Brazilian regulation. The trueness of the method was evaluated using two CRMs and the addition and recovery technique.
Development of preconcentration methods for determination of trace elements and speciation of chromium and arsenic in agricultural samples
Keywords: MIP OES; LC-ICP-MS; SPE; CPE; Coprecipitação; Especiação química; Matriz Doehlert; Elementos traço; Pescado; Fertilizante orgânico; Coprecipitation; Chemical speciation; Box-Behnken; Doehlert matrix; Trace elements; Fish; Organic fertilization; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA